Land-use classification and mapping using landsat imagery for GIS database in Langkawi Island - Ahmad, Zuhairi; Azman, Nur Shahira Azlyn; Md. Rosli, Nur Suhaila; Mustapa, Mohd Zaini (Zibeline International Publishing, 2020)
This study examined the land use changes in Langkawi Island for over 12 years. Land use maps were derived by analysing temporally available satellite imageries of that area. Subsequent Landsat imageries of the years 2006, 2014 and 2018 were processed in Environment for Visualising Images (ENVI) software using Normalize Differences Built-Up Index (NDBI) and supervised classification. The land use classes obtained were categorised according to the Soil and Water Assessment Tool (SWAT) land use classification namely URLD, URMD, URHD, FRSE, UINS, UIDU, URTN, RICE, AGRR, and WATR. The analysis of the land use maps provides a comparison for the area of land use class around Langkawi Island based on the Rancangan Kawasan Khas 2020 (RKK). This study will give an overview of the stakeholder on the current land use of Langkawi Island for future land use planning. Moreover, the land use map generated in this study can be used as a functional land use input for the SWAT model and provide a temporal Geographic Information System (GIS) database on the land use of the Langkawi Island.